2022
DOI: 10.1037/lhb0000477
|View full text |Cite
|
Sign up to set email alerts
|

Severity matters: The moderating effect of offense severity in predicting racial differences in reporting of bias and nonbias victimization to the police.

Abstract: Objective: Previous research has noted contradictory findings regarding race and police notification, such that Black people indicate higher levels of distrust in the police yet report victimization to the police at rates similar to or higher than others. We investigated the role of offense severity in accounting for these discrepancies. Hypotheses: We hypothesized that severity would moderate racial differences in reporting, such that Black victims would be less likely to report less severe victimization but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…Clear condemnation of xenophobia is an essential measure for countering the attitudes we observe here ( Lunn et al, 2020 ). Second, anti-Asian prejudicial attitudes were surprisingly frequent, even pervasive, in our sample, and research has suggested both that consistent exposure to bias and discrimination may be related to acute mental health consequences, depression, or event desensitization (see Lantz et al, 2022 ; Wenger et al, 2022 ; Wenger & Lantz, 2021 ), and that Asian victims of discrimination are less likely than others to seek help after victimization ( Lantz & Wenger, 2021 ). Following this, researchers and policymakers should make efforts to develop appropriate interventions aimed at addressing these consequences.…”
Section: Discussionmentioning
confidence: 73%
“…Clear condemnation of xenophobia is an essential measure for countering the attitudes we observe here ( Lunn et al, 2020 ). Second, anti-Asian prejudicial attitudes were surprisingly frequent, even pervasive, in our sample, and research has suggested both that consistent exposure to bias and discrimination may be related to acute mental health consequences, depression, or event desensitization (see Lantz et al, 2022 ; Wenger et al, 2022 ; Wenger & Lantz, 2021 ), and that Asian victims of discrimination are less likely than others to seek help after victimization ( Lantz & Wenger, 2021 ). Following this, researchers and policymakers should make efforts to develop appropriate interventions aimed at addressing these consequences.…”
Section: Discussionmentioning
confidence: 73%
“…For example, in general, reasons why someone does not report a crime to the police is that they may be ashamed, embarrassed, afraid of retaliation, fearful they will not be believed, or think the police will not handle the incident seriously (Brunson and Wade 2019; Felson et al 2002; Felson, Messner, and Hoskin 1999; Fisher et al 2003; Xie and Baumer 2019). When considering the situational correlates of reporting to the police, extant research has demonstrated that factors that reflect incident severity – such as weapon use, presence of multiple offenders, or injury – tend to be reliably related to reporting behaviors and are informed by rationality related to decision-making processes (Goudriaan, Lynch, and Nieuwbeerta 2004; Graham, Kulig, and Cullen 2019; Lantz, Wenger, and Malcom 2022; Muniz and Powers 2021; Xie and Baumer 2019; Zavala 2010). Situational correlates that capture the severity of the incident are also linked to the stress the event causes the victim (Greenberg and Barry Ruback 1985).…”
Section: Reporting Of Victimizationmentioning
confidence: 99%
“…Given that other research has demonstrated that hate crime is geographically concentrated as well ( Wenger & Lantz, 2021a ), future research should consider spatial variation in the mental and physical consequences of the COVID-19 pandemic on bias and hate crime as well. Next, these results highlight the potential magnitude of underreporting issues with official hate crime statistics ( Lantz et al, 2022 ; Myers & Lantz, 2020 ). In the current study, we surveyed 575 Asian Americans, and discovered that at least 112 (19.5%) of them had been the victim of at least one racially-motivated hate crime incidents.…”
Section: Discussionmentioning
confidence: 81%